ATOPIC DERMATITIS IN PEDIATRIC POPULATION: EFFECT OF RISK FACTORS ON AGE AT ONSET AND SEVERITY - Tanzeela Khalid; Ayesha Sajid (Journal of University Medical & Dental College, 2014)
ABSTRACT OBJECTIVES: To study the effect of family history of atopy, maternal education and duration of breast feeding on age at onset and severity of atopic dermatitis PATIENTS AND METHODS: Study design: observational study, cross-sectional survey One hundred pediatric patients with atopic dermatitis (AD) attending Dermatology or Pediatrics departments of Madinah Teaching Hospital, Faisalabad, from Jan to March, 2014 were enrolled using convenience sampling. Information regarding demographics, family history of atopy, maternal education and breast feeding were recorded on a structured questionnaire. The children were examined by a consultant Dermatologist, for clinical signs of atopic dermatitis. Severity of AD was calculated for each patient using SCORAD index RESULTS: Patients with a family history of atopy had significantly less severe disease at presentation (p= .048) than those with no family history of atopy. Patients who were breast fed for less than 6 months and 6 months to 1 year developed AD earlier than those who were breast fed for 13- 24 months (p=.033). The effect of maternal education on age at onset and severity of AD was not significant. CONCLUSION: Children with AD may present earlier with a relatively mild disease if they have a positive family history of atopy. Breast feeding for more than one year may have a protective effect by delaying the age of onset. Maternal education has no effect on age of onset and severity of AD.